O "morar" na velhice: expectativas entre envelhescentes - Martines, Maria Guiomar de Simone (2008)
A world-wide phenomenon that is occurring is the growth of the aged population. Brazil also presents this increase of the participation of the population with 60 years or more in the national population, due to reduction in the fertility taxes/mortality and to the increase of the life expectancy of the people. With this change in the social panorama it has necessity to adjust the scientific resources, medical, social and until cultural for this new reality. The proposal of this work is to transit for the new concepts of the aging and to evaluate the panoramas Brazilian and world-wide with focus in liveing for people who will become soon in oldness. The objective of this qualitative research was of raising between elderly individuals (phase that precede the 60 years) its expectations of liveing, which its representations on the diverse forms known of liveing in the oldness, and the distrusts that happen of this subject. The personal income and with the activity of work or academic had been evaluated 12 citizens divided in 4 subdivided groups in accordance with. In the results we observe that the representations and the speech on liveing in the oldness if relate very with the individual experiences and its representations, and although the sample to be small, of the one not to observe significant differences between the groups, the differences are really individual, as well as its histories. It has little planning on aging and liveing, and for many, to be submitted to the research was interesting to raise the subject. We perceive that it is a subject that still lacks of very study, social and preventive work, it becomes what it still more interesting